Effect of surface treatments on the shear bond strength of luting cements to Y-TZP ceramic - Sciasci, Plínio [UNESP]; Abi-Rached, Filipe Oliveira [UNESP]; Adabo, Gelson Luis [UNESP]; Baldissara, Paolo; Fonseca, Renata Garcia [UNESP] (Elsevier, 2015)
Statement of problem Because zirconia is a glass-free material, alternative surface treatments such as airborne-particle abrasion or silica coating should be used for long-term bonding. However, these surface treatments in combination with different bonding agents and luting cements have not yet been studied. Purpose The purpose of the study was to evaluate the effect of surface treatments on the shear bond strength (SBS) of luting cements to Y-TZP ceramic. Material and methods Zirconia disks (N=240) were airborne-particle abraded with the following particles (n=48): 50 μm Al2O3; 120 μm Al2O3; 30 μm silica-coated Al2O3 (Rocatec Soft); 120 μm Al2O3+110 μm silica-coated Al2O3 (Rocatec Plus); and Rocatec Plus. After silanization of the zirconia surface, composite resin disks were bonded with (n=12) RelyX Luting 2; RelyX ARC; RelyX U100; and Panavia F. The bonded specimens were thermocycled (10 000 cycles) and tested for SBS. Failure mode was determined with a stereomicroscope (×20). The morphology and elemental composition of airborne-particle abraded surfaces were evaluated with scanning electron microscopy (×500) and energy-dispersive x-ray spectroscopy (×50). Results Surface treatments, cements, and their interaction were significant (P<.001). For RelyX ARC, Rocatec Soft and Rocatec Plus provided the highest SBS. In general, surface treatments did not influence the SBS of RelyX U100 and Panavia F. Regardless of the cement, no significant difference was found between 50 μm and 120 μm Al2O3 particles, between Rocatec Soft and Rocatec Plus, or between Rocatec Plus and 120 μm Al2O3 particles+Rocatec Plus. All groups showed adhesive failures. Different particle sizes provided differences in morphological patterns. The elemental composition comprised Al and Al/Si for alumina and silica-abraded zirconia. Conclusions Particle size did not influence the SBS of the groups abraded exclusively with alumina or silica-coated particles. RelyX ARC was more surface-treatment dependent than RelyX U100 or Panavia F.
Keywords: Zircônia; Cerâmicas dentárias; Cimentos resinosos; Adesão|Prótese dentária; Materiais odontológicos